Exercise-induced asthma screening of elite athletes: field versus laboratory exercise challenge - Rundell, K. W.; Wilber, R. L.; Szmedra, L.; Jenkinson, D. M.; Mayers, L. B.; Im, J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose of this study was to compare a laboratory based exercise challenge (LBC) to a field based exercise challenge (FBC) for pulmonary function test (PFT) exercise-induced asthma (EIA) screening of elite athletes. Methods: Twenty-three elite cold weather athletes (14 men, 9 women) PFT positive for EIA (FBC screened) served as subjects. Twenty-three gender and sport matched controls (nonasthmatics) were randomly selected to establish PFT reference values for normal elite athletes. Before FBC, athletes completed a medical history questionnaire for EIA symptoms. FBC evaluations consisted of baseline spirometry, actual or simulated competition, and 5, 10, and 15 min postexercise spirometry. PFT positive athletes were evaluated in the laboratory using an exercise challenge simulating race intensity (ambient conditions: 21°C, 60% relative humidity). PFT procedures were identical to FBC.